Structural model and dynamic analysis of six-axis Cartesian coordinate robot for sheet metal bending. (12th July 2019) - Xu, Fengyu; Jiang, Quansheng; Rong, Lina; Zhou, Pengfei; Hu, Jinlong
Bending is an important procedure for processing sheet metals, while it is a key link in the realization of automatic processing of sheet metal. To improve the efficiency and accuracy of bending processing, this article proposed a structure model and a prototype of a six-axis Cartesian coordinate robot for sheet metal bending to replace workers completing automatic bending processes. Based on the analysis of overall structure schemes of the robot, kinematic simulation is conducted by using the automatic dynamic analysis of mechanical system (ADAMS). Furthermore, the dynamic performance of the structural model of the robot for sheet metal bending is analysed and design optimization is performed. A prototype of the robot based on the optimal structural model of six-axis Cartesian coordinate robot for sheet metal bending is made. Finally, under the work conditions, the efficiencies and accuracies of sheet metal bending by a worker and the robot are compared and tested. The structural model of six-axis Cartesian coordinate robot for sheet metal bending presented in this article is found to be applicable to sheet metal bending robot and improves the stability of sheet metal bending machine. The laboratory testing and experimental results verified the feasibility of the proposed robot.